UJI AKTIVITAS ANTIOKSIDAN DAN FORMULASI SEDIAAN BODY SCRUB KOMBINASI KOPI ROBUSTA (COFFEA CANEPHORA) DAN BERAS PUTIH (ORYZA SATIVA L.) - Nanang Saiful Imron; Endang Setyowati; Emma Jayanti Besan (Nusantara Hasana Journal, 2025)
Skin aging is a natural thing that will occur, because humans experience a slowdown in the process of skin cell renewal and collagen production. Body skin care such as body scrubs are used for the purpose of maintaining, caring for skin smoothness, brightening the skin so that it is not dull and releasing dead skin cells. This study aims to evaluate the physical quality and determine the antioxidant activity in the body scrub preparation in combination with robusta coffee and white rice. Organoleptic evaluation of body scrub cream preparations including color, smell and texture. pH testing uses a pH meter that is pre-calibrated using a standard buffer solution. The homogeneity test was carried out by applying 0.5 grams of the preparation to the glass object and then covering it with other glass. The adhesion test aims to find out the preparation when it adheres to the skin. The antioxidant test by way of a 100 ppm test solution is made in a series of concentrations of 20, 40, 60, 80, 100 ppm. The results of this study tested the organoleptic, the 5% formula has a semi-dense texture, dark grayish, the formula 10% and 15% are dark blackish, with a typical aroma of coffee. The best pH research results in the 10% formula are pH 7.50. For FI, FII, FIII meet the requirements of pH physical characteristics test, homogeneity, dispersibility and adhesion test. The results of antioxidant activity DPPH method concentrations of 5%, 10%, and 15% respectively were 66.17; 63,26; 62.56 ppm, which means that its antioxidant activity is strong. The conclusion of this study is that the combination of robusta coffee and white rice can be formulated into a body scrub preparation and has strong antioxidant activity (50-100). The best formulation at a concentration of 15% is 62.56 ppm.